Effect of Photodynamic Inactivation of Propionibacterium Acnes Biofilms by Hypericin (Hypericum perforatum) - Barroso, R. A.; Navarro, R.; Tim, C. R.; Ramos, L. P. [UNESP]; Oliveira, L. D. de [UNESP]; Araki, A. T.; Macedo, D. B.; Fernandes, K. G. Camara; Assis, L. (Springer Nature, 2022)
The colonisation of the pilosebaceous follicle by Propionibacterium acnes (P. acnes) is known as one of the main factors driving acne by taking part in the inflammatory response of the skin. Antimicrobial Photodynamic Therapy (aPDT) has important applicability in skin diseases, however its use with hypericin (Hypericum perforatum) photosensitizer for inhibit of P. acnes have not yet been clarified. The aim of this study was to evaluate in vitro the effects of aPDT using hypericin photosensitizer associated with red low-level laser therapy on P. acnes biofilms. The biofilms were placed in 96-well microplates by using standard suspensions (2 × 107 CFU/mL) and grown in BHI broth for 48 h in anaerobic chamber. Subsequently, the control group received application of 0.9% sterile saline solution for 3 min (C); laser groups received irradiation of energies of 3 J (L3J); hypericin group at concentrations of 15 μg/ml for 3 min (H15%); aPDT group received 15 μg/ml concentration of hypericin associated with laser energy of 3 J (H15%L3J). After the biofilms were broken up and seeded for CFU counting. The results showed a reduction in P. acnes biofilms in H15% and H15%L3J. In addition, this reduction was higher in H15%L3J. This study showed that hypericin and aPDT using hypericin photosensitizer showed effective antimicrobial action for inhibiting P. acnes biofilms and may be promising resources in the clinical treatment of acne vulgaris.
Keywords: Acne Vulgaris; Antimicrobial photodynamic therapy; Hypericin; Photochemotherapy; Photosensitizing agents; Propionibacterium